보존적 치료에 반응하지 않는 소아 청소년 편평족의 수술 - 김휘택(Hui Taek Kim); 박원석(Won Seok Park); 김학상(Hak Sang Kim) (The journal of the Korean Orthopaedic Association, 2022)
목적: 단순 편평족은 소아나 청소년에서 흔하며 대개 치료가 필요하지 않다. 그러나 동반 이상이 있는 경우 보존적 치료를 하더라도 증상이 지속될 수 있다. 본 연구는 보존적 치료에 반응하지 않는 편평족에서 동반된 이상을 조사하고 수술적으로 치료한 결과를 분석하였다. 대상 및 방법: 통증과 보행 이상을 보이는 46 편평족에 대해 연부조직 및 뼈를 포함한 다중 술식으로 치료한 31명(15명 양측, 16 명 편측; 여자 11명, 남자 20명)을 대상으로 후향적 분석을 하였다. 수술 당시 평균 나이는 10.9세였다. 동반 이상에 대해 체질량지수(비만＞95퍼센타일), Beighton의 연부조직 과잉 운동성(Beighton 점수 5 이상), Silfverskiöld 검사법을 통해 아킬레스건이나 비복근의 조임, 외반슬, 대퇴골 전염각이나 경골의 과 염전 및 기타 다른 족부 이상을 컴퓨터 단층촬영과 자기공명영상 촬영을 이용해 분석하였다. 임상적 치료 결과는 수술 후 2년 이상 된 23족에 대해 Oxford Ankle Foot Questionnaire for Children (OxAFQC)과 중족 및 후족부 American Orthopaedic Foot Ankle Society (AOFAS) 점수를 이용하여 분석하였다. 결과: 총 31명 중 11명에서 연부조직 과잉 운동성과 7명에서 비만을 보였다. 치료한 46예의 편평족과 동반된 이상으로 아킬레스건이나 비복근의 조임(42족), 부주상골 증후군(16족), 하지 뼈 회전 이상(11족[대퇴골 전염각 감소 7예, 경골 외염전 증가 4예])과외반슬(3명, 6족)이 있었다. 치료는 아킬레스건 연장술(43족), 대퇴골 및 경골 회전 절골술(12족), 원위 대퇴골/근위 경골에 일시적편측 골단 유합술(6족)을 시행하였다. 편평족에 대해서는 비골건 연장술(3족), 후경골건 전진술(8족), 종골 내반 절골술(10족), 종골-입방골-설상골을 포함하는 3C 족근골 절골술(24족)을 시행하였다. 23족에 대한 OxAFQC 점수는 수술 전에 비해 향상되었으며 (p＜0.05), 최종 AOFAS 점수는 중족부 94.9±7.7, 후족부 96.0±6.7이었다. 결론: 소아 청소년에서 보존적 치료에 반응하지 않고 통증을 가지거나 보행 이상을 보이는 편평족의 경우 동반 이상이 있을 수 있으므로 이에 대한 세밀한 분석이 증상의 병태생리학을 이해하고 성공적인 치료를 위해 필요하다. Purpose: Simple flatfoot is common in children and adolescents, and usually does not require treatment. On the other hand, symptoms can occur when underlying abnormalities are present and continue even after treatment. This study examined the accompanied abnormalities in a flatfoot unresponsive to conservative treatment. Materials and Methods: Forty-six symptomatic flatfeet in 31 patients (15 bilateral; 16 unilateral; 11 females and 20 males) who undergone multiprocedural surgical treatment (mean age at the time of surgery, 10.9 years), were studied retrospectively. The accompanying comorbidities were evaluated: BMI (obesity>95%tile), joint laxity and hypermobility by the Beighton score (5 or more points of the Beighton score), Achilles tendon or gastrocnemius muscle tightness by the Silfverskiöld test, and bony malalignment (genu valgum or femoral and tibial torsion) and other foot disorders by computed tomography and magnetic resonance imaging. The surgical results for 23 feet (follow-up period after surgery>2 years) were evaluated by Oxford Ankle Foot Questionnaire for Children (OxAFQC) and mid- and hindfoot American Orthopaedic Foot Ankle Society (AOFAS) scores. Results: Of 31 patients 11 had soft-tissue hypermobility, and seven had obesity. Of 46 symptomatic flatfeet, comorbidities included Achilles tendon (or gastrocnemius muscle) tightness (42 feet), symptomatic accessory navicular (16), lower extremity malalignment (11) (seven decreased femoral anteversion, and four increased tibial external torsion), and genu valgum (six in three patients). Achilles tendon lengthening (43 feet) and femoral and tibial rotational osteotomy (12), and temporary hemiepiphysiodesis (six) were performed. For the flatfoot, peroneal tendon lengthening (three feet), posterior tibial tendon advancement (8), calcaneal varus osteotomy (10), and calcaneuscuboid- cuneiform (3C) osteotomy (24) were performed. For 23 feet, changes in mean OxAFQC scores before and after surgery were significant (p<0.05). The midfoot and hindfoot AOFAS scores at the last follow-up were 94.9±7.7 and 96.0±6.7, respectively. Conclusion: Symptomatic flatfoot unresponsive to conservative treatment can involve a concomitant abnormality in children and adolescents. Hence, a thorough systemic evaluation is required to understand the pathophysiology and for successful treatment after surgery. KCI Citation Count: 0